Strategi Manajemen Pemasaran Usaha PP. Riyadlul Jannah Pacet Mojokerto Perspektif Ilmu Ekonomi Syariah - M. ZIDNY NAFI' HASBI ZIDNY NAFI' (POINT: Jurnal Ekonomi dan Manajemen, 2021)
Marketing strategy is very important for a company, both small and large companies, especially when they want to develop the company and increase the number of consumers, as well as companies owned by PP. Riyadlul Jannah Pacet Mojokerto, there are many businesses owned by PP. Riyadlul Jannah Pacet Mojokerto includes the Meriah Kitchen Restaurant, M2M ,. Agri Bisnis, Rijan Mart, Franchese, Grilled Chicken Wong Solo, Shake Noodle Mang Uci Bandung, Quick Chicken, Organic Vegetable Mayur, Giant Super Market, Hero Super Market, Chicken Slaughterhouse, Rijan Mineral Water. The research method used is a qualitative method which includes data sources both primary data and secondary data, data collection techniques namely observation, interviews, documentation, data analysis techniques namely editing and organizing, checking the validity of the data, and the research stage. All of this researchers use to find research results. Exposure data which contains an overview of the object of research and data obtained from interviews and other documents related to marketing, then a discussion contains the strategic strategies used to market the product and the constraints and solutions. The conclusion of this discussion is that the strategy used is a strategy to promote promotion through advertising, 5S services, 4M services (Cheap, Easy, Steady, Moment), and giving free, then product packaging which includes determining or selecting brend and expanding product selection. However, all of this is in accordance with sharia economic values, namely the absence of trickery, absence of gharar, and benefiting both parties.